Correction to: User satisfaction with public oral health services in the Brazilian unified health system - Leonardo de Paula Amorim; Maria Inês Barreiros Senna; Gizelton Pereira Alencar; Lorrany Gabriela Rodrigues; Janice Simpson de Paula; Raquel Conceição Ferreira (BMC, 2019)
Following publication of the original article [1], the authors have reported that there is an error in Table 2 - Distribution of users concerning satisfaction with oral health services: the categories 'No' and 'Yes' should swap places.